Financial Performance Effect on Credit Distribution in Banking Sector - Nyolinda, Jesslyn; Ariesa, Yeni; Erika, Erika; Veri, Veri (Budapest International Research and Critics University, 2021)
The purpose of this research is to evaluate the relationship of_LDR, ROA, NPL, CAR towards credit supply of BEI-listed banking sector within the period of 4 years, which is during 2016-2019. The method utilized for this research is descriptive quantitative. There are 45 companies at the banking sector listed by BEI, however only 26 companies fulfill the criteria according to the sampling purposive technique; in which we will consider as the sample of this research.The data processing involves the usage of Structural Equation Model (SEM) with Partial Least Square (PLS) approach. PLS analysis is conducted by using the software SmartPLS 3.0. The result of data processing shows partially that variable LDR, ROA and NPL has positive relationship towards credit supply of the banking sector. On the other hand, variable CAR shows a partial negative relationship towards credit supply of the banking sector. Simultaneously, all four variables has a significant relationship towards the credit supply. It is signified by the amount of R2 which is 13,5%, and the rest of 86,5% is influenced by other factors.